Penerapan Costumer Due Dilligence (CDD) dalam Pencegahan Pendanaan Terorisme melalui Perbankan (Faculty of Law, Maranatha Christian University, 2016)
With the increasingly widespread crime of terrorism in Indonesia lately, required the efforts of law enforcement authorities to combat such crimes. The crime of terrorism is very closely related to the financing of terrorism, because terrorism crime plan will not run without their financial support. Financing of Terrorism is deeds in order to provide, collect, give, or lend funds, either directly or indirectly for use / carry out terrorist activities, terrorist organization or a terrorist. In contrast to the Money Laundering Act that aim to disguise the origin of the assets, then the purpose of the crime of terrorism financing is helping terrorism activities, both with wealth that is the result of a crime or of property that is acquired legally. There is a phenomenon inwhich usually use Bank as its media because Bank is a financialinstitution that guarantee the privacy and confidentiality of its customer as confidential Bank.To face the increasing number of terrorist financingactivites, the Bank apply the Customer Due Diligence (CDD)where’s one of Bank’s obligation is reportingthe suspicious customer’s transaction to Indonesian Financial Transaction Reports and Analysis Centre (INTRAC).This may open the possibility of sharing the customer information into Indonesian Financial Transaction Reports and Analysis Centre (INTRAC) or authorities which is actually non-compliace with Bank secrecy legal principle. This paper use normative juridical research method with an analytical description in order to understand the process of Customer Due Diligence (CDD) and implementation of Combating Terrorist Financing into Bank secrecy.